Dynamics Modeling and Modal Analysis of Machine Tool Considering Joints Parameters - Liao, Yongyi; Liao, Baiyu (Manufacturing Technology Journal, 2019)
Based on analysis of joint dynamic characteristics to obtain dynamic values of combined surface incorporating joint dynamic data, a method for dynamics modeling of machine tool considering joint dynamic characteristics is developed and analyzed. The machine tool is simplified and modeled by selecting the motion coordinates of each component in accordance with the structure characteristics and the vibration displacement for each component in exciting test. According to the way and condition of the joints, the equivalent dynamic parameters of each joint are determined by applying the general joint surface dynamic data. Calculation methods of dynamic parameters for some typical joints in machine tool structures are analyzed and described. Taking a horizontal milling machine as an example, the machine is simplified into a dynamic model with 21 degrees of freedom, the calculated results of dynamic characteristics correspond to that of exciting test and modal analysis. The modeling method is effective and applicable in machine tool design and structure improvement.
Keywords: Machine tool; Modeling; Dynamic model; Joints parameters; Dynamic characteristics